RESEARCH ON THE STRESS-STRAIN STATE OF A PUNCH DURING HOLE PUNCHING IN THIN SHEET METAL USING NUMERICAL MODELING - KOSTIUK, NAZAR; TYMCHUK, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In modern mechanical engineering, stamping and hole punching thin sheet metal are crucial operations. Production efficiency, part precision, and economic viability depend directly on tool quality and durability, especially the punch. This article thoroughly investigates the stress-strain state of a punch, a key factor determining its service life and reliability. We specifically analyze the punch's interaction with 1 mm thick sheet metal, a typical scenario in industries from automotive to household appliances.To study this complex mechanical phenomenon, we used an advanced numerical modeling approach: the Finite Difference Method (FDM). FDM effectively handles complex geometries and non-linear material behaviors common in metal deformation. The entire model and calculations were implemented using Python, which allowed for rapid model creation, modification, and integration with visualization and data analysis tools. This approach provided high flexibility and accuracy, enabling detailed modeling of dynamic punching processes. Our research includes a comprehensive comparative analysis of results for different punch diameters. We systematically evaluated how geometric parameters influence the distribution of internal stresses and deformations, crucial for understanding tool strength and failure susceptibility. We also simulated variations in punch material based on strength indicators, including different tool steel grades with distinct mechanical properties like yield strength, ultimate tensile strength, and Young's modulus. This analysis helped identify optimal materials for maximum tool durability against cyclic loads, abrasive wear, and impact stresses. Results showed that proper material selection significantly extends punch service life, reducing replacement and maintenance costs.Using numerical modeling, we constructed detailed 3D and 2D graphs of stress distribution (specifically, von Mises equivalent stresses) throughout the punch volume. These visualizations clearly identified areas of high stress concentration and precisely located critical zones where crack initiation and intense tool wear are most likely. Pinpointing these "hot spots" is vital for developing punch strengthening strategies. The modeling also allowed us to analyze stress dynamics during punching, revealing peak loads that could lead to instantaneous failure.The results are highly valuable for practical application in mechanical engineering. They directly aid in optimizing punch design, enabling engineers to create more robust and durable tools that withstand repeated loading cycles without degradation. This involves refining cutting edge geometry, radii, grinding angles, and other features affecting stress distribution. Furthermore, the modeling results help predict punch longevity and prevent premature failure, which is essential for reducing production downtime and operational costs. Applying this numerical modeling methodology opens new opportunities for innovation in stamping tool design, enhancing their reliability and economic efficiency.
Keywords: punch; stamping; punching; stress; deformation; numerical modeling; finite difference method; Python; wear; design; sheet metal; strength; durability; optimization; tool; simulation; tribology; materials science; engineering design